Assessing the Contemporary Issues of Countering Transnational Crime - Ivan Kubariev; Yevgen Barash; Valeriy Pcholkin; Olena Pluzhnik (Jurnal Cita Hukum, 2021)
Crimes are always considered as inevitable in every given society operating under an organized system of operation. Sometimes this crime has to cross borders constituting huge threat to country sovereignty and integrity. With all this in place, States are usually confronted in establishing possible forms and methods of combating the so called transnational crimes. Specific examples of successful experience of developed countries, such as the United States, Canada and Western European countries, are analyzed. The author's definitions of the terms "transnational crime", "method of combating transnational crime" and "form of combating transnational crime" are given. It is stated that the problem of the existence and expansion of transnational crime in the form of shadow illegal activities of criminal organizations is one of the greatest threats of our time. It is stated that in connection with the commission of illegal acts by members of transnational criminal organizations of various orientations, the definition of the essence and content of this socially dangerous phenomenon is a non-trivial matter. It is emphasized that the modern scientific community reflects the desire to clearly establish and specify the current methods of combating transnational crime and to implement their appropriate classification. It is noted that both domestic and foreign scholars in the field of law classify methods of combating transnational crime according to a set of different criteria and factors. Scholars also emphasize the importance of intensifying effective international cooperation in this area.Keywords: Form; Method; Transnational Crime; International Cooperation; Criminal Organization Menilai Isu Kontemporer Melawan Kejahatan Transnasional AbstrakKejahatan selalu dianggap sebagai sesuatu yang tak terelakkan dalam setiap masyarakat yang beroperasi di bawah sistem operasi yang terorganisir. Terkadang kejahatan ini harus melintasi batas negara yang merupakan ancaman besar bagi kedaulatan dan keutuhan negara. Dengan semua ini, Negara biasanya dihadapkan pada kemungkinan bentuk dan metode untuk memerangi apa yang disebut kejahatan transnasional. Contoh-contoh spesifik dari pengalaman sukses negara-negara maju, seperti Amerika Serikat, Kanada dan negara-negara Eropa Barat, dianalisis. Definisi penulis tentang istilah "kejahatan transnasional", "metode pemberantasan kejahatan transnasional" dan "bentuk pemberantasan kejahatan transnasional" diberikan. Disebutkan bahwa masalah keberadaan dan perluasan kejahatan transnasional berupa kegiatan ilegal bayangan organisasi kriminal merupakan salah satu ancaman terbesar di zaman kita. Disebutkan bahwa sehubungan dengan dilakukannya perbuatan melawan hukum yang dilakukan oleh anggota organisasi kriminal lintas negara dari berbagai orientasi, maka pengertian esensi dan isi dari fenomena bahaya sosial ini bukanlah hal yang sepele. Ditekankan bahwa komunitas ilmiah modern mencerminkan keinginan untuk secara jelas menetapkan dan menentukan metode terkini untuk memerangi kejahatan transnasional dan untuk menerapkan klasifikasi yang sesuai. Perlu dicatat bahwa baik sarjana dalam dan luar negeri di bidang hukum mengklasifikasikan metode memerangi kejahatan transnasional menurut seperangkat kriteria dan faktor yang berbeda. Para ahli juga menekankan pentingnya mengintensifkan kerja sama internasional yang efektif di bidang ini.Kata kunci: Bentuk; Metode; Kejahatan Lintas Negara; Kerjasama internasional; Organisasi Kriminal Оценка Современных Проблем Противодействия Транснациональной ПреступностиАннатацияПреступления всегда считаются неизбежными в каждом обществе, действующем в рамках организованной системы действий. Иногда это преступление должно пересекать границы, представляя огромную угрозу суверенитету и целостности страны. При наличии всего этого государства обычно сталкиваются с проблемой установления возможных форм и методов борьбы с так называемыми транснациональными преступлениями. Анализируются конкретные примеры успешного опыта развитых стран, таких как США, Канада и страны Западной Европы. Даны авторские определения терминов «транснациональная преступность», «метод борьбы с транснациональной преступностью» и «форма борьбы с транснациональной преступностью». Констатируется, что проблема существования и распространения транснациональной преступности в виде теневой противоправной деятельности преступных организаций является одной из самых серьезных угроз современности. В связи с совершением противоправных действий членами транснациональных преступных организаций различной направленности определение сущности и содержания этого общественно опасного явления является нетривиальным вопросом. Подчеркивается, что современное научное сообщество отражает стремление четко установить и конкретизировать существующие методы борьбы с транснациональной преступностью и внедрить их соответствующую классификацию. Отмечается, что как отечественные, так и зарубежные ученые в области права классифицируют методы борьбы с транснациональной преступностью по набору различных критериев и факторов. Ученые также подчеркивают важность активизации эффективного международного сотрудничества в этой области.Ключевые слова: форма, метод, транснациональная преступность, международное сотрудничество, преступная организация